2001
DOI: 10.1590/s1519-566x2001000300007
|View full text |Cite
|
Sign up to set email alerts
|

Gamasida (Arachnida: Acari) Edáficos de Piracicaba, Estado de São Paulo

Abstract: -The objectives of this work were to identify the edaphic mites collected in Piracicaba, State of São Paulo, and to determine the specific predominance in each of the environments studied. Soil samples were collected in three different environments, namely in an area of secondary forest, an area of perennial crops, represented by a rubber tree plantation (Hevea brasiliensis Müll. Arg.), clone RRIM 600 and an area of annual crops (corn followed by bean). Litter samples were collected in the patch of secondary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
23

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 12 publications
2
12
0
23
Order By: Relevance
“…However, Smith et al (1998) reported a slightly higher number of ologamasid than of rhodacarid mites in the Montane Cordillera Ecozone of Canada. The low numbers of rhodacarids observed in this study agree with the data obtained recently by Mineiro & Moraes (2001). In that study, the authors recovered only a few rhodacarids from soil and from litter layers in a rubber tree (Hevea brasiliensis Müll.…”
Section: Regionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, Smith et al (1998) reported a slightly higher number of ologamasid than of rhodacarid mites in the Montane Cordillera Ecozone of Canada. The low numbers of rhodacarids observed in this study agree with the data obtained recently by Mineiro & Moraes (2001). In that study, the authors recovered only a few rhodacarids from soil and from litter layers in a rubber tree (Hevea brasiliensis Müll.…”
Section: Regionsupporting
confidence: 92%
“…Mites of that family were rare in the areas where this study was conducted. Similarly, no digamasellids were found by Mineiro & Moraes (2001) in the study referred to above.…”
Section: Regionmentioning
confidence: 74%
See 1 more Smart Citation
“…MINEIRO & MORAES (2001) consiguieron que la mayor abundancia de ácaros Mesostigmata provenientes de hojarasca de un bosque secundario en São Paulo, Brasil estuvo representada por Ologamasidae (57,5%) y Podocinidae (9,4%), mientras que en la hojarasca de caucho se encontró que Laelapidae fue colectada en mayor porcentaje (26,3%), seguido de Phytoseiidae (25,5%). Probablemente, la mayor abundancia de Macrochelidae observada en el presente estudio este relacionada con el método de muestreo puesto que, con las trampas de caída también fueron colectados una amplia variedad de artrópodos, principalmente insectos, que llevaban estos ácaros sobre su cuerpo debido al hábito forético de Macrochelidae.…”
Section: Resultados Y Discusiónunclassified
“…Vásquez et al (2007) registraron mayor abundancia en la familia Macrochelidae (80,1%), seguido de Ameroseiidae, Ologamasidae y Phytoseiidae en el matorral, mientras que en el Bosque Deciduo, Macrochelidae (27,5%) fue señalada como la más abundante seguida de Parasitidae (20,3%), Ascidae (15,5%), Parholaspidae (9,7%) y Laelapidae (9,2%). Por otra parte, Mineiro & Moraes (2001) señalaron que los mayores porcentajes de colecta correspondieron a Ologamasidae (57,5%) y Podocinidae (9,4%) en el bosque secundario, mientras que en la hojarasca de caucho se encontró que Laelapidae fue colectada en mayor porcentaje (26,3%), seguido de Phytoseiidae (25,5%).…”
Section: Materiales Y Métodosunclassified